Evaluating the Regional Contracted Teachers Appointment Program at the Junior High School Level in Tambrauw Regency, Southwest Papua Province : Context of Education in Remote Areas - Hariyanto, Teguh; Ismanto, Bambang (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to assess the achievements and impacts of the program regarding the appointment of contract teachers at the junior high school (SMP) level in Tambrauw Regency, Southwest Papua Province. This research used an evaluation method with the Context, Input, Process, and Product (CIPP) Evaluation Model developed by Stufflebeam. Respondents consist of representatives from the Department of Education, School Principals, and Teachers. Data collection methods include interviews, observations, and document studies. The collected data are then analyzed qualitatively and presented verbally. The utilization of triangulation and qualitative analysis methods in this study enhances the credibility of the data and the validity of the resulting findings. The analysis results indicate that: Firstly, in terms of context, the implementation of this program still aligns with the existing needs. Secondly, in terms of input, the program can proceed due to the availability of adequate financial support and resources. Thirdly, during the implementation process, external interventions influence the achievement of program objectives. Lastly, in terms of product, this program successfully achieves its predetermined goals and positively impacts the improvement of educational quality. In conclusion, the program regarding the appointment of contract teachers in junior high schools in Tambrauw Regency has a significant impact on enhancing the quality of education. This assessment is crucial for refining and optimizing existing programs. This study provides a valuable contribution to the program evaluation literature, particularly in the context of education in remote areas.